2021
DOI: 10.21831/ep.v2i1.40129
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran menyenangkan sebagai upaya menanggulangi pandemi Covid-19

Abstract: Artikel ini bertujuan untuk menjelaskan konsep dan prosedur praktis model pembelajaran joyful learning dalam rangka pelatihan guru di Gantiwarno Klaten yang dilakukan oleh Tim PPM dari Departemen Kurikulum dan Teknologi Pendidikan. Pembelajaran yang menyenangkan di dalamnya terdapat hubungan yang kuat antara pendidik dan siswa, tanpa merasa terpaksa atau merasa tertekan. Relasi antara guru dan siswa nampak perlu dirubah dalam posisi egaliter. Perkembangan teknologi informasi memungkinkan siswa mendapatkan info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…And in the end the achievement of learning objectives will not be maximized. Through fun learning can build a strong relationship between educators and students, without feeling forced or pressured (Pujiriyanto et al, 2021). This statement further strengthens that students who feel happy in learning will be more enthusiastic and motivated in learning.…”
Section: Fun Learning Is a Need For Studentsmentioning
confidence: 58%
See 1 more Smart Citation
“…And in the end the achievement of learning objectives will not be maximized. Through fun learning can build a strong relationship between educators and students, without feeling forced or pressured (Pujiriyanto et al, 2021). This statement further strengthens that students who feel happy in learning will be more enthusiastic and motivated in learning.…”
Section: Fun Learning Is a Need For Studentsmentioning
confidence: 58%
“…Sulthon emphasized again (2016) in his research study that learning that is oriented to student activity can help students become more independent in learning. Pujiriyanto, et al (2021) from the results of his research concluded that the application of constructivist learning methods can facilitate fun learning for students. With the constructivist learning method, students become active subjects in learning activities according to their socio-cultural needs and context.…”
Section: Fun Learning Is a Need For Studentsmentioning
confidence: 99%
“…Tim pengajar melakukan hal ini dalam upaya membuat lingkungan belajar ramah dan tidak kenal takut, serta membuat siswa menikmati waktu mereka di kelas. agar siswa mudah memahami atau menerima isinya (Pujiriyanto, 2021).…”
Section: Pendahuluanunclassified
“…Pembelajaran menyenangkan bertujuan untuk didapatkannya pemahaman dan penyikapan sehingga pembelajaran dapat berlangsung secara benar dan efektif (Pujiriyanto, P 2021). Pembelajaran menyenangkan memerlukan suatu bahan ajar berupa media pembelajaran.…”
Section: Pendahuluanunclassified